A case report on dealing with complications of hypertension during child birth - Kaparwan, Arti; Godiyal, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Hypertensive disorder in pregnancy is a major source of morbidity and mortality worldwide. This is a disease unique to pregnancy typically characterized by blood pressure ≥140/90 mm of Hg after 20 weeks of pregnancy and associated with proteinuria 300 mg/24 hours or 1+ dipstick. If left untreated the disorder often leads to serious maternal and perinatal complications. Here there is a case report of women with undiagnosed hypertension during pregnancy which complicates life of both mother and fetus by complicating labour and birth with precipitate labour and postpartum haemorrhage. This is a preventable complication by educating women about importance of routine antenatal visits.